Three-Phase Oscillator with Cascade Ability Using Voltage Current Conveyor - Seangrawee Buakaew; Wipavan Narksarp; Kamonthip Choeysombat; Juthamas Kanjanawiwin; Narin Atiwongsangthong; Weera Pengchan (My University, 2024)
This paper presents a new circuit configuration employing voltage current conveyors (VCII) in conjunction with a minimal number of passive elements to achieve a voltage mode sinusoidal oscillator with a 3 -phase differential output. The proposed circuit features a straightforward architecture, with all passive elements connected to low-impedance nodes. Consisting solely of identical VCIIs without multiple outputs, the circuit facilitates the cascading of the 3 -phase outputs without requiring supplementary buffering. Simulation results obtained through PSPICE, along with experimental validation using commercial ICs, are provided to substantiate the efficacy of the proposed circuit.
Keywords: Analog and Mixed-Signal Circuit Design; Advancements in PLL and VCO Technologies; Radio Frequency Integrated Circuit Design